Oral ulcers as an early manifestation of histoplasmosis - Rosa, Beatriz; Macedo, Debora; Ortega, Karem; Lemos, Celso; Gallottini, Marina; Martins, Fabiana (Journal of Oral Diagnosis, 2024)
Histoplasma capsulatum, the causative agent of histoplasmosis, is an uncommon systemic fungal illness that represents significant health risks to people living with HIV/AIDS (PLHV), especially those who are residents in endemic regions like Brazil. While oral histoplasmosis is rare, this observation can serve as a significant indicator of compromised immunological state, particularly in those with low numbers of TCD4+ cells. This study intends to examine recent literature on oral histoplasmosis and to provide a case of oral manifestations as the first indication of disseminated histoplasmosis in a young woman recently diagnosed with HIV.